Pemanfaatan Teknologi Digital dalam Edukasi Gizi: Pengembangan Aplikasi Eduzire untuk Pencegahan Dini Kejadian Stunting Pada Fase Remaja: Use of Digital Technology in Nutrition Education: Development of the Eduzire Application for Early Prevention of Stunting in Adolescence - Emilia, Esi; Rosmiati, Risti; Hanifa, Zulfa Nur (Universitas Airlangga, 2026)
Background: Adolescence is a crucial stage for stunting prevention. Adequate nutritional intake, healthy lifestyle practices, and digital-based nutrition education are essential to support optimal growth and to break the intergenerational cycle of stunting. Objectives: To develop and test the feasibility and effectiveness of the Eduzire application in improving adolescent nutrition knowledge scores as part of an early prevention strategy for stunting. Methods: This study used a Research and Development (R&D) approach with the Define, Design, Develop, and Disseminate (4D model). Sixty high school students in Deli Serdang were involved, consisting of 25 in the trial stage and 35 in the implementation stage. Instruments included needs analysis, nutrition knowledge tests, expert validation, and satisfaction analysis. Results: The analysis at the Define stage showed respondents’ average nutrition knowledge was 57% (low); 92% had never used a nutrition education app, 88% did not know how to calculate nutritional status, and 91.7% wanted an application that could assess dietary intake and provide nutrition education. The design stage developed features such as Z-score calculation, individual nutrient requirements, daily intake records, balanced nutrition, anemia and stunting materials, and online consultation with nutrition experts. The development stage validation by experts showed feasibility scores of 82% and 84%, whereas the Disseminate stage demonstrated a 24% increase in nutrition knowledge and 90% user satisfaction. Conclusions: The Eduzire application serves as a nutrition education medium with the potential to enhance adolescents’ nutrition knowledge as an effort to prevent stunting from school age.